Oral Impact on Quality of Life Among Young Adults in Iași - Alice Murariu; Carmen Hanganu; Roxana Vasluianu (Romanian Journal of Oral Rehabilitation, 2012)
The aim of the study is to assess the impact of oral health on quality of life of the adult population, 18-34 years in Iasi, Romania. Methods A cross-sectional survey was conducted in 2011 and was selected a sample of 174 subjects with the age between 18-34 years old. The subjects were clinically examined according to WHO criteria and oral health related quality of life was assessed with the Oral Health Impact Profile-14 and Eurobarometer questionnaires. Results The most affected quality of life dimension was psychological discomfort, reported by 31% of the young adults. Some aspects, like functional limitation, difficulty to relax, and handicap are no affected. Other negative effects registered were associated with irritability (6.9%) and interrupted meals (5.7%). Using Eurobarometer questionnaire we found that 88% of the patients are unsatisfied with general and oral insurance system, and only 21.4% are confidence in a better future. Conclusions Clinical indicators like “prosthodontic and surgical treatment needs” provide a sensitive predictor for negative impact on psychological dimensions of the quality of life.